Espace urbain et gentrification aux États-Unis, évolution des interprétations - Laurence Gervais-Linon (Anglophonia)
Since the 1980’s, North American urban space has changed radically. Industrial neighborhoods that turned into slums then ghettos with the changing of the American economy and the post Second World War urban sprawl are today encountering "revitalization," "urban renewal" and "gentrification."These different phenomena have been studied through the concept of Frontier—converting urban decay and violence into new chic—and the process of capital mobility, itself attracting new social classes from a new economy based in the inner city (Neil Smith). Other studies show that post-industrial urban space is very similar to pre-industrial urban space, such as that of the Renaissance cities. (Kotkin) But Gentrification could be much more than this, a part of a much larger shift in the political economy and culture of the late 20th and early 21st century.This paper focuses on the various theories linked to the radical reapropriation of many central and inner cities in North America in the past three decades.